2020
DOI: 10.3390/ma13194394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Particle Size of Al/Ni Multilayer Powder on the Exothermic Characterization

Abstract: In this study, the exothermic temperature performance of various Al/Ni multilayer powders with particle sizes ranging from under 75 to over 850 µm, which generate enormous heat during self-propagating exothermic reactions, was determined using a high-speed sampling pyrometer. The Al/Ni multilayer powders were prepared by a cold-rolling and pulverizing method. The multilayer constitution of the Al/Ni multilayer powders was examined by observing the cross-section of the powders using scanning electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Gas-phase synthesis includes physical/chemical deposition [ 12 ] and magnetron sputtering technique [ 13 ]. Solid-phase synthesis includes self-propagating high-temperature synthesis (SHS) [ 14 ], thermal explosion [ 15 ], hot gas extrusion [ 16 ], spark plasma sintering [ 17 ], rolling [ 18 , 19 ], hot isostatic pressing [ 20 ], mechanical alloying [ 21 ] and shock-wave loading (SWL) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase synthesis includes physical/chemical deposition [ 12 ] and magnetron sputtering technique [ 13 ]. Solid-phase synthesis includes self-propagating high-temperature synthesis (SHS) [ 14 ], thermal explosion [ 15 ], hot gas extrusion [ 16 ], spark plasma sintering [ 17 ], rolling [ 18 , 19 ], hot isostatic pressing [ 20 ], mechanical alloying [ 21 ] and shock-wave loading (SWL) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, to improve the productivity and convenience of the heat source, an Al/Ni multilayer powder fabricated by the coldrolling and frictional pulverizing methods was developed, and the thermal reaction characteristics were studied. 13,[25][26][27][28] In a previous study, we revealed that the exothermic reaction characteristics, such as the reaction speed and maximum exothermic reaction temperature, increase with an increase in the number of cold-rolling passes. 25) These characteristics can be controlled to some extent by changing the rolling conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Since RSM components, as a rule, are powders, they must be consolidated. There are various technologies to consolidate RSMs into a monolithic structure: radial forging [1,6], cold and hot isostatic pressing [7,8], high-pressure torsion [9], magnetron sputtering [10] and cold spraying [11,12], cold rolling [13,14], accumulative roll-bonding [15], and explosive compacting [5,16]. The disadvantages of sputtering are its low rate and high cost.…”
Section: Introductionmentioning
confidence: 99%